Analysis of Quality and Comparison of Benefits of Seaweed (Eucheuma cottonii) in Bungin Permai Village, Tinanggea District, South Konawe Regency - Sari, Elda Amalia; Nurdiyanty, Iin; Tamtama, Ary (Agrikan Jurnal Agribisnis Perikanan, 2024)
This research aims to determine the quality analysis and comparison of profits from selling seaweed (Eucheuma cottonii) in Bungin Permai Village, Tinanggea District, South Konawe Regency. This research method uses purposive sampling by taking samples from three different seaweed farmers and analyzing the quality of seaweed (Eucheuma cottonii) three times. The results of this research show: sensory analysis with a standard SNI value of 7 in the number range 5-8, water content 30-35%, foreign object content ranging from 80.31 - 85.28. Analysis of impurities levels ranged from 2.17%, - 3.15%. The average income from Seaweed (Eucheuma cottonii) in Bungin Permai Village is IDR 132,148,667 with total costs of IDR 152,351,333 and total revenue of IDR 284,500,000, the amount of revenue obtained by seaweed farming is calculated using the following calculations. the difference between total revenue minus total costs. The return cost ratio (R/C) value is 1, it can be seen that seaweed farming has an R/C value of 1.867, meaning that seaweed farming is feasible to run or make a profit.